FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN WISATAWAN NUSANTARA BERWISATA BELANJA DI RAMA KRISNA OLEH-OLEH KHAS BALI - Adi Sumara Putra, I Kadek; Suwena, I Ketut; Kusuma Negara, I Made (Jurnal IPTA (Industri Perjalanan Wisata); Vol 5 No 1 (2017): Jurnal IPTA (July 2017), 2017)
The activities of shopping trips into one of the attractions which is most favorite by domestic tourists. It can be seen from the percentage of domestic tourists who’s doing activity for shopping tour that is equal to 35 percent. The tourism shopping center that are currently being developed and are Frequently visited by domestic tourists is Rama Krishna Oleh-Oleh Khas Bali as a tourism shopping center of handicrafts from Bali with modern nuances. The purpose of this study was to determine the factors influencing the domestic tourists decision who’s doing activities for shopping trips and also determine the dominant factors that influence the domestic tourists decision for shopping trips in Rama Krishna Oleh-Oleh Khas Bali. This research using purposive sampling with distributing questionnaires to 374 respondents who traveled shopping at Rama Krishna Oleh-Oleh Khas Bali. The data were collection by observation, questionnaire interview, and library research. This research is being tested first for its validity and reliability before being by factor analysis. The results of this research showed that 18 variables were identified, 15 variables were selected into the three factors that influence the domestic tourists decision for shopping trips. Those factors consist of psychological factors with eigenvalue of 5.587, situational factors with eigenvalue of 1.594, and external factors with eigenvalue of 1.117. From the result of analysis factors well known that the most dominant factor were influencing domestic tourists decision for shopping trips in Rama Krishna Oleh-Oleh Khas Bali is a psychological factor because it has the highest eigenvalue of all factors that have been formed. The variables included in the psychological factors are: motivation, personality, learning, attitudes, and perceptions.
Keywords: Buying Decision, Shopping Tourism, Factor Analysis